Pouring Out of One Vessel into Another: Originality and Imitation in Two Modern Adaptations of Tristram Shandy. (17th August 2018) - Seager, Nicholas
Abstract: Laurence Sterne's Tristram Shandy (1759–67) appears to resist adaptation. Its verbal density, narrative complexity, and self-conscious bookishness mark it out as intensely medium-specific. However, its richly allusive style, scepticism about conventions of representation, and involvement of readers may make it a model for contemporary approaches to adaptation. This essay analyses two re-mediations: Martin Rowson's 1996 graphic novel and Michael Winterbottom's 2005 movie. It argues that these artists use Sterne to fashion virtuosic originality within a culture of mimicry and pastiche. To this end, they produce self-conscious adaptations that reveal and reflect on their own creative processes. The essay proposes that moving beyond axiological and teleological views of adaptation will be facilitated by recognizing literary classics as themselves acts of appropriation which in turn solicit acts of adaptation.